2021
DOI: 10.4055/cios20111
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Bone Mineral Density and Knee Osteoarthritis (Kellgren-Lawrence Grade): Fifth Korea National Health and Nutrition Examination Survey

Abstract: Background Osteoarthritis (OA) and osteoporosis (OP) are the 2 most common bone disorders associated with aging. We can simply assume that older patients have a higher incidence of OA and OP with more severity. Although several papers have conducted studies on the relationship between OA and OP, none of them has demonstrated a conclusive link. In this study, we used radiological knee OA and bone mineral density (BMD; T-score of the total hip and lumbar spine) to analyze the incidence of OA and OP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Abdin-Mohamed M. et al,(2009) 21 proving that BMD of tibia do not increase in presence of knee OA; this result is in line with another recent study which illustrated that BMD was lower in moderate-to-severe OA states. 22 As already pointed out in a previous paper, it is possible to claim confidently the ensemble of purpose, experimental strategy (mainly, signal acquisition and processing workflows), and the promising findings obtained represent, to the best of the authors’ knowledge, a partially unexplored strategy in this field, which sets this study apart from others. Moreover, as already we claimed, 4 there were no studies which presented and evaluated the predictive power of similar 3D features extracted on MRI and CT data of the knee joint.…”
Section: Resultssupporting
confidence: 51%
“…Abdin-Mohamed M. et al,(2009) 21 proving that BMD of tibia do not increase in presence of knee OA; this result is in line with another recent study which illustrated that BMD was lower in moderate-to-severe OA states. 22 As already pointed out in a previous paper, it is possible to claim confidently the ensemble of purpose, experimental strategy (mainly, signal acquisition and processing workflows), and the promising findings obtained represent, to the best of the authors’ knowledge, a partially unexplored strategy in this field, which sets this study apart from others. Moreover, as already we claimed, 4 there were no studies which presented and evaluated the predictive power of similar 3D features extracted on MRI and CT data of the knee joint.…”
Section: Resultssupporting
confidence: 51%
“…A recent study demonstrated that BMD was the highest when the knee OA was mild, and was significantly lower in moderate and severe OA. Generally, it is considered that the severity of OA increases and the level of BMD decreases with increasing age [ 51 ]. The different correlations between data could be due to the restricted number of participants, their characteristics, outcome measures or the status of the knee joint (as it is in the early stage).…”
Section: Discussionmentioning
confidence: 99%
“…Other partial findings also support the reduction of bone density in osteoarthritis (Schreiber et al, 2018;Muhlenfeld et al, 2021;Zhu Z. et al, 2021). A review in regard to the relationship between BMD and osteoarthritis of the knee by Choi et al (2021) showed that patients with moderate and severe OA had significantly lower BMD than the normal ones. Patients with mild OA show an increase in BMD but this is most likely caused by a temporary increase in score due to high turnover of the osteoarthritic subchondral bone (Dequeker et al, 2003).…”
Section: The E Ects Of Irisin On Osteoarthritis Irisin and Bone Miner...mentioning
confidence: 76%